(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Maternal health is a cornerstone of global healthcare initiatives, given its critical impact on maternal and neonatal outcomes. This article discusses common obstetric complications, including gestational diabetes, hypertensive disorders, and infections, emphasizing their clinical management and preventive strategies. The integration of modern diagnostic tools, enhanced antenatal care, and multidisciplinary approaches to treatment forms the foundation of improving maternal health globally.